Early hominin biogeography in Island Southeast Asia. Issue 5 (September 2015) - Larick, Roy; Ciochon, Russell L.
<x xml:space="preserve">Abstract</x> Island Southeast Asia covers Eurasia's tropical expanse of continental shelf and active subduction zones. Cutting between island landmasses, Wallace's Line separates Sunda and the Eastern Island Arc (the Arc) into distinct tectonic and faunal provinces. West of the line, on Sunda, Java Island yields many fossils of Homo erectus. East of the line, on the Arc, Flores Island provides one skeleton and isolated remains of Homo floresiensis. Luzon Island in the Philippines has another fossil hominin. Sulawesi preserves early hominin archeology. This insular divergence sets up a unique regional context for early hominin dispersal, isolation, and extinction. The evidence is reviewed across three Pleistocene climate periods. Patterns are discussed in relation to the pulse of global sea‐level shifts, as well as regional geo‐tectonics, catastrophes, stegodon dispersal, and paleogenomics. Several patterns imply evolutionary processes typical of oceanic islands. Early hominins apparently responded to changing island conditions for a million‐and‐a‐half years, likely becoming extinct during the period in which Homo sapiens colonized the region.